2014
DOI: 10.1175/jtech-d-13-00230.1
|View full text |Cite
|
Sign up to set email alerts
|

Aerial Imaging of Fluorescent Dye in the Near Shore

Abstract: Aerial images are used to quantify the concentration of fluorescent Rhodamine water tracing (WT) dye in turbid and optically deep water. Tracer releases near the shoreline of an ocean beach and near a tidal inlet were observed with a two-band multispectral camera and a pushbroom hyperspectral imager, respectively. The aerial observations are compared with near-surface in situ measurements. The ratio of upwelling radiance near the Rhodamine WT excitation and emission peaks varies linearly with the in situ dye c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
62
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 41 publications
(64 citation statements)
references
References 22 publications
(20 reference statements)
0
62
0
Order By: Relevance
“…The 2.4. Inner-Shelf Dye Aerial Remote Sensing Novel aerial observations of nearsurface dye concentration were obtained from a small plane with a multispectral camera system and coupled global positioning and inertial navigation systems [Clark et al, 2014]. Two cameras captured images near the peak excitation and emission wavelengths of the fluorescent Rhodamine WT.…”
Section: Ib09 Experiments Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The 2.4. Inner-Shelf Dye Aerial Remote Sensing Novel aerial observations of nearsurface dye concentration were obtained from a small plane with a multispectral camera system and coupled global positioning and inertial navigation systems [Clark et al, 2014]. Two cameras captured images near the peak excitation and emission wavelengths of the fluorescent Rhodamine WT.…”
Section: Ib09 Experiments Methodsmentioning
confidence: 99%
“…The georeferenced aerial images are combined into mosaics and regridded onto a rectangular grid with 2 m 3 2 m lateral resolution. See Clark et al [2014] for details.…”
Section: Ib09 Experiments Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Grant et al (2005) analysis showed that alongshore flux of surfzone water is at least 50 to 300 times larger than the crossshore flux of surfzone water. Clark et al (2014) used fluorescent dye and aerial imaging technique to study the nearshore mixing. Feddersen (2007) studied breaking wave induced cross-shore tracer dispersion in the surfzone.…”
Section: Introductionmentioning
confidence: 99%